2020
DOI: 10.3122/jabfm.2020.05.200050
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Parent Voices into a Pediatric Research Network Through a Virtual Parent Panel

Abstract: Background: Additional strategies are needed for longitudinal engagement of parents as key stakeholders in practice-based research networks (PBRNs). Our objective was to create a virtual Parent Panel for our PBRN to engage parents remotely and use their input on child health research. Methods: We used an existing online parent survey study to invite parents to participate longitudinally by completing brief, monthly online questionnaires about child health research topics. The existing survey assessed perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…To our knowledge, this is one of the first PABs to engage youth members for bidirectional conversations with researchers with the goal of enhancing pediatric research participation. Previous PABs and pediatric research networks have been reported, but are either focused on clinical experiences or do not incorporate the voices of children, relying instead on parents, child health advocates, and pediatric specialists to guide and protect youth research participants [11][12][13]. In this study, we share the experiences and insights of adolescent PAB members and their parents on the benefits of participating in the PAB and providing feedback on research studies involving youth participants.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is one of the first PABs to engage youth members for bidirectional conversations with researchers with the goal of enhancing pediatric research participation. Previous PABs and pediatric research networks have been reported, but are either focused on clinical experiences or do not incorporate the voices of children, relying instead on parents, child health advocates, and pediatric specialists to guide and protect youth research participants [11][12][13]. In this study, we share the experiences and insights of adolescent PAB members and their parents on the benefits of participating in the PAB and providing feedback on research studies involving youth participants.…”
Section: Discussionmentioning
confidence: 99%
“…The use and impact of parent or mother advisory groups has not been well documented in the pediatric literature; however, there has been significant research supporting the involvement of caregivers in medical decision-making to improve patient outcomes [ 9 , 10 , 24 , 25 , 26 , 27 ]. While there is still a scarcity of published data, the use of parents in the development of pediatric interventions has been increasing in the last decade, as parent involvement can improve pediatric research engagement by increasing participant enrollment and retention, contributing to the development of interventions and measurement tools, and identifying potential issues in a research project [ 19 , 24 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 Additional strategies such as virtual solutions are now needed as PBRNs consider how to facilitate longitudinal engagement of stakeholders and the needs for virtual engagement created by COVID-19. Engster et al 22 describe the creation of a virtual Parent Panel to engage parents remotely and use their input for child health research. The authors utilized an existing research study on pain management during routine child vaccinations to develop regular communication with a group of parents/patient stakeholders to provide feedback on research ideas.…”
mentioning
confidence: 99%